Pemberdayaan Masyarakat Berbasis Dakwah Melalui Pendekatan Participatory Action Research di Desa Bontolanra: Da’wah-Based Community Empowerment Through A Participatory Action Research in Bontolanra Village - M. Kasim (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2026)
This community service program aimed to implement Islamic values through religious development activities. The program was conducted in Desa Bontolanra, Kecamatan Galesong Utara, Kabupaten Takalar, using the Participatory Action Research (PAR) approach, which positioned the community as the primary subject throughout the stages of problem identification, planning, implementation, evaluation, and follow-up. Data were collected through observation, interviews, and documentation, then analyzed qualitatively using the Strengths, Opportunities, Aspirations, Results (SOAR) framework. The implementation process consisted of preparation, program planning, implementation, evaluation, and sustainability planning stages. The programs included Qur’anic learning activities (TK/TPA), school teaching, Tebar Imam and Da’i, Amal Jama’i, Pesantren Kilat (PESKIL), Ta’lim Remaja, and other socio-religious activities. The findings indicate that integrating PAR and SOAR successfully increased community participation in religious activities, strengthened mosque-based empowerment, improved children’s enthusiasm for Qur’anic learning, enhanced youth engagement in Islamic activities, and increased awareness of religious practices and moral development. The programs also contributed to strengthening social cohesion, mosque functions as community development centers, and collaboration between higher education institutions and local communities. Despite challenges such as limited implementation time and varying levels of participation, this study demonstrates that participatory-based religious empowerment has significant potential to create sustainable socio-religious transformation within rural communities.